Not "Just" an Undergrad: Undergraduate Journals as a Portal to Participating in Academic Discourse Communities - Paige France; Christopher Eaton (Arizona State University, 2023)
This essay examines a case study that investigated how students learned and how they applied their writing skills as they pursued publication in an undergraduate scientific journal at a Canadian university. As we conducted a genre analysis of student drafts submitted to the journal and interviewed students who published in the journal's inaugural year, we noted the desire and eagerness that students had to publish at the undergraduate level. We also noticed certain barriers to students fully participating in research for their discourse communities, including challenges accessing publication opportunities and revising their work for new audiences and contexts. Undergraduate journals offer a tremendous space for them to hone a variety of skills in a supportive environment while also taking the first steps to fully participating in scholarly practice.